Nutritional Management of Laying Hens for Extended Production Cycles: Evaluation of a Hybrid Feeding Strategy - Ugalde, Xabier Arbe (Journal of Poultry Sciences and Avian Diseases, 2025)
Extending laying cycles to 100 weeks or more presents significant nutritional challenges for modern high-producing hens. Traditional age-based feeding strategies may no longer meet the birds’ evolving physiological needs. This study evaluates H&N International’s Hybrid Feed system, which integrates pre-lay and early production nutrition into a unified, performance-based approach. Introduced at 17 weeks and maintained until approximately 70% egg production, the Hybrid Feed features reduced energy density, elevated amino acids, moderate fiber, and a high proportion of coarse calcium. Results show improved body weight, feed intake, and metabolic adaptation during early lay. The system supports targeted egg size management through amino acid adjustments and emphasizes energy intake driven by body weight and environment. A three-phase feeding model, with nutrient modifications tailored to production stages rather than age, is proposed. This strategy enhances eggshell quality, skeletal integrity, and overall productivity, offering a dynamic nutritional framework for extended-cycle layer management.